REPRESENTASI KEGIATAN HUMAS DALAM FILM THE QUEEN : Analisis Semiotika Roland Barthes - Wildan Achmad Fauzi, (2020)
The title of this research is "Representation of Public Relations Activities in The Film of the Queen (Roland Barthes Semiotic Analysis)". The purpose of this study is to reveal the representation of public relations values and the depiction of good public relations practice in the film of The Queen and prove that film artwork can also be an alternative learning media. This study uses a qualitative interpretative research method and uses Roland Barthes's semiotic approach. Data collection methods in this study are divided into two types namely primary data and secondary data, primary data in the form of scenes in the film Queen are selected into thirteen units of analysis and secondary data in the form of literature studies and interviews if needed. The collected data will be analyzed the meaning of denotation, connotation and myth using the Roland Barthes semiotic approach. After the denotative and connotative meanings are obtained, the writer analyzes the representation of his public relations activities by aligning the meanings that have been obtained with the functions, roles, and values of public relations. In this study the authors found six public relations roles undertaken by Tony Blair, namely Expert Prescriber / expert advisor, communication technician, communication facilitator, facilitator in the problem solving process, evaluating public opinion, and managing emergencies, as well as three public relations functions including issue management, Press Agentri, and also internal relations. The author also found three public relations values, namely the value of expertise, Loyalty, and Advocacy.